The cross and other Jewish stories - Shapiro, Lamed, 1878-1948 (New Yiddish library., 2007)
Lamed Shapiro (1878-1948) was the author of groundbreaking and controversial short stories, novellas, and essays. Himself a tragic figure, Shapiro led a life marked by frequent ocean crossing, alcoholism, and failed ventures, yet his writings are models of precision, psychological insight, and daring. Shapiro focuses intently on the nature of violence: the mob violence of pogroms committed against Jews; the traumatic after-effects of rape, murder, and powerlessness; and, the murderous event that transforms the innocent child into witness and the rabbi's son into agitator. Within a society on the move, Shapiro's refugees from the shtetl and the traditional way of life are in desperate search of food, shelter, love, and things of beauty. Remarkably, and against all odds, they sometimes find what they are looking for. More often than not, the climax of their lives is an experience of ineffable terror. This collection also reveals Lamed Shapiro as an American master. His writings depict the Old World struggling with the New, extremes of human behaviour combined with the pursuit of normal happiness. Through the perceptions of a remarkable gallery of men, women, children - even of animals and plants - Shapiro successfully reclaimed the lost world of the shtetl as he negotiated East Broadway and the Bronx, Union Square, and vaudeville.